Islamic Entrepreneurship Research Since 1990: A Systematic Literature Review - Rafiki, Ahmad; Hidayat, Sutan Emir; Pananjung, AlFatih Gessan (LPPM, Universitas Islam Syarifuddin Lumajang, 2023)
This study aimed to explore the progress of the Islamic entrepreneurship literature by examining the various thematic research areas and try to draw a map on Islamic entrepreneurship through a systematic review. There are 274 documents revealed from the reputable database called Scopus since 1990. This paper also includes the conceptual framework and discussion on important things related to the Islamic entrepreneurship. This study finds the root and details information on the Islamic entrepreneurship researches which had been done in more than 30 years as well as the issues related to the Islamic entrepreneurship. It also finds the data on the prominent authors, reputable journals, productive institutions, and supportive countries on the Islamic entrepreneurship studies. Despite having limitations, one of them is relying on one database (Scopus), it still gives huge information on the Islamic entrepreneurship research. A comprehensive insights and pictures would be benefited the researchers, academicians and practitioners able to formulate any crucial plans and strategies related to the research on Islamic entrepreneurship.